A Functional Model of Workplace Envy and Job Performance: When do Employees Capitalize on Envy by Learning from Envied Targets? - Lee, KiYoung; Duffy, Michelle K. (Academy of Management Journal, 2019)
We integrate the social functional view of emotions with recent developments in workplace envy research to develop and test a novel theoretical framework showing that envious employees can use their envy to promote self-enhancing actions rather than other-diminishing behaviors. We theorize that enviers’ core self-evaluations and friendship ties will attenuate the extent to which enviers undermine envied targets and promote the extent to which enviers actively learn from their envied targets through observational learning and advice seeking. Using two data sets from round-robin surveys of employees in the cosmetic (Study 1) and the financial (Study 2) industries, we show that, while enviers undermine envied targets, they also capitalize on their envy by seeking advice from the envied targets, and enviers who have higher core self-evaluations and friendship with the envied targets are more likely to seek advice from those targets; higher core self-evaluation also decreases the likelihood of undermining the envied targets. We found limited support for the role of envy in triggering enviers’ observational learning. Furthermore, enviers who learn from envied targets perform better and advice seeking is more influential for enviers’ performance than observational learning.